V-Y advancement flap for repair of neglected injuries of the Achilles tendon using 2 mini-incisions - Matías-Joannas, Germán; Casola, Leandro; Arrondo, Guillermo; Niño Gomez, Daniel; Labbate, Santiago (Journal of the Foot & Ankle, 2020)
Objective: To find a safe repair site for a proximal mini-incision to expose the fascia at the level of the gastrocnemius medialis (GM) myotendinous junction (MTJ). Methods: Seventeen anatomic specimens of popliteal fossa, leg, and foot fixed in formalin were dissected, and the perpendicular distance from the apex of the medial malleolus to the GM MTJ was measured. Results: The minimum and maximum perpendicular distances from the apex of the medial malleolus to the GM MTJ were 14.00cm and 20.5cm, respectively. Average distance was 16.56cm. Conclusion: We were able to establish a constant value and the average GM MTJ height, which allows for V-Y lengthening through 2 mini-incisions. In reviewing the literature, there was no description of the approaches proposed in this study. Level of Evidence VI; Therapeutic Studies; Case Series.Achilles tendon/surgery